State administrative assets report as sufficient preliminary evidence in the crime of corruption - Nur Chusniah,; Sudarsono,; I Nyoman Nurjaya,; Abdul Madjid, (Technium Social Sciences Journal, 2021)
The type of research used in this research is normative legal research. The State Organizing Assets Report as an administrative document can be used as a legal document as sufficient initial evidence in a criminal act of corruption. Sufficient preliminary evidence is interpreted as a minimum of 2 (two) pieces of evidence as stipulated in Article 184 of the Criminal Procedure Code, namely witness statements, expert statements, letters, instructions and statements of the defendant. The State Organizing Assets Report is an extension of documentary evidence considering that the State Organizing Assets Report is made according to the provisions of the law, is required to be reported to the Corruption Eradication Commission and those who don’t comply are subject to sanctions and are intended to prove a thing or condition so that it meets the criteria for the instrument documentary evidence as referred to in Article 187 letter d of the Criminal Procedure Code.